An Examination of the Thinking Styles of Undergraduates who Study at Universities that Provide Sports Training - Gacar, Atalay (Kamla-Raj Enterprises, 2015)
In this study, the researchers examined The Thinking Styles of Undergraduates Who Study at Universities That Provide Sports Education. A total of 330 students from various universities participated in the study. A personal information form was used to gather the participants' demographical information and the Rational Experiential Inventory (REI) was used to determine their thinking styles. SPSS was used to analyze the collected data at a five percent (p<0.05) level of significance. In conclusion, it was ascertained that there is a significant difference between men and women with regards to the sub-dimension of need for cognition factor regarding thinking styles points of the senior students from different academic departments. Furthermore, it was observed that men have more need for cognition than women.
Keywords: Thinking Styles; Physical Education and Sports Teaching; Sports Management; Coaching; Recreation